Short-Term Efficacy and Safety Outcomes of Brolucizumab in the Real-Life Clinical Practice - Andrea Montesel (Frontiers Media S.A., 2021)
To report the early efficacy and safety outcomes of treatment with intravitreal injections of brolucizumab (IVT-B) in patients presenting neovascular age-related macular degeneration (nAMD) in a tertiary clinical setting. A retrospective case series of patients that received IVT-B with a minimum of two injections performed and at least 4 weeks of follow-up after last injection. Nineteen eyes of 19 patients were included. The number of IVT-B performed for the whole cohort was 58 injections; the mean number of IVT-B per patient was 3.0 ± 1.0 (range 2–6); the mean follow-up time was 14.4 ± 9.0 weeks. Mean baseline best-corrected visual acuity was 0.4 ± 0.4 logMAR and at the last follow-up was 0.4 ± 0.6 logMAR (p = 0.778). All eyes showed a reduction in retinal thickness, with the central macular thickness being 470 ± 151 μm at baseline and 360 ± 144 μm at the last follow-up (p = 0.001). Intra-retinal fluid was present at baseline in 12 eyes (63%) and in three eyes (16%) at the last follow-up (p = 0.065). Sub-retinal fluid was present at baseline in 17 eyes (89%) and at the last follow-up in three eyes (16%, p = 0.011). Pigment epithelium detachment was apparent in the 16 eyes (84%) at baseline and was still present in 14 eyes (73%, p = 0.811). One adverse event of intraocular inflammation was reported. In conclusion, our short-term experience showed that brolucizumab was highly effective in restoring the anatomy and in stabilizing the visual acuity of eyes with nAMD. Its safety profile should be evaluated carefully and needs further investigations.